ENHANCING TECHNIQUES FOR FOOD STOCK OPTIMIZATION - Karthikeyan A; Anbuselvan S; Anbuchezhiyan V; Aswin M (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Food waste production is on the rise, and this is a national and international issue. It has several aspects, all of which stand to gain from a comprehensive grasp of the volume and kind of food waste produced over the whole food production and consumption cycle. The effect that food waste has on the production of greenhouse gas emissions, such carbon dioxide and methane, is the main source of worry for many stakeholders. However, there is also rising interest in using food waste as a resource input for agriculture, as well as growing worries about the environmental and economic sustainability of the current food waste disposal systems. In this project, we can put in place a food waste management system to raise awareness of food wastes and the harmful effects of undesired, underused human trash and junk. We can also create a system for knowledge-based management that ensures wastes are effectively managed with the least amount of waste possible and yields useful results. We can implement two types of modules such as admin and user module. Admin module can be collecting all food details with location information and also orphanage home details. And managing food wastage with proper delivery to poor people or proper disposal management. User module can also post address to collect wastage foods from their locations. This project can be implemented in real time as software for user friendly access.